The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s11892-016-0744-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel Therapeutics for Diabetes: Uptake, Usage Trends, and Comparative Effectiveness

Abstract: The number of available therapies for treating type 2 diabetes has grown considerably in recent years. This growth has been fueled by availability of newer medications, whose benefits and risks have not been fully established. In this study, we review and synthesize the existing literature on the uptake, efficacy, safety, and cost-effectiveness of novel antidiabetic agents. Specifically, we focus on three drug classes that were introduced in the market recently: thiazolidinediones (TZDs), dipeptidyl peptidase-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 41 publications
0
16
1
1
Order By: Relevance
“…Whilst previous studies have reported sitagliptin to be weight neutral in patients with DM, a mixed response was recorded in our cohort 10. Two patient maintained stable weight, one achieved reduction and two others had weight gain.…”
Section: Discussioncontrasting
confidence: 52%
“…Whilst previous studies have reported sitagliptin to be weight neutral in patients with DM, a mixed response was recorded in our cohort 10. Two patient maintained stable weight, one achieved reduction and two others had weight gain.…”
Section: Discussioncontrasting
confidence: 52%
“…Long-term evidence on clinical outcomes, safety and economic implications of new antidiabetic drugs are limited in the literature. Such evidence is even more limited on the direct comparison between medicines not grouped by pharmacological class [55]. Budgetary and logistical impact assessments will also aid decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Observational epidemiological studies have suggested that some anti-hyperglycemic agents could affect cancer risk [3] , [6] . Patients with DM treated with sulphonylureas or insulin had a higher risk of CRC than other patients, whereas metformin use may be beneficial in primary prevention of CRC [3] , [5] , [6] , [7] , [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Observational epidemiological studies have suggested that some anti-hyperglycemic agents could affect cancer risk [3] , [6] . Patients with DM treated with sulphonylureas or insulin had a higher risk of CRC than other patients, whereas metformin use may be beneficial in primary prevention of CRC [3] , [5] , [6] , [7] , [8] . The dose-dependent relationship between metformin and CRC has been reported [9] , [10] , [11] ; however, long-term epidemiological observations between metformin and CRC are rarely reported.…”
Section: Introductionmentioning
confidence: 99%